Способи маскування та виявлення технічних засобів відеоспостереження - Гребенчук, М. В.; Олейнікова, О. І. (ХНУРЕ, 2022)
This work is devoted to the issue of video surveillance and possible ways to hide video surveillance devices. Below are some of the most popular options based on the research of modern scientists. As the number of atrocities in the world has increased in the 21st century, the world needs to be guarded and protected from terrorism and misconduct. As practice shows, video surveillance devices help to solve this problem.